Historical characterization of diurnal rainfall variation of the Philippines - PEREZ, DARWIN D. (Archīum Ateneo, 2017)
Diurnal rainfall variability on Philippine land areas is investigated using the Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA) 3B42 three-hourly dataset. Annual and monthly averages of TRMM diurnal rainfall data from 2000-2014 is clustered into four distinct clusters using the K-means clustering. Vertical winds, relative humidity and moisture convergence variables from the European Center for Medium-Ranged Weather Forecasts (ECMWF) ERA-Interim (EIN75) are used to examine the dynamics behind the diurnal rainfall pattern and seasonal variations in the patterns of clustering. We compare TRMM diurnal rainfall pattern with individual ground stations and EIN75 to assess its accuracy and check the compatibility respectively. The correlation with station data is highest in high elevation areas where the monsoon winds have the lowest magnitude and strong land/sea breeze is coupled with strong mountain breeze. Correlation decreases as the monsoon winds influence on the clusters increases. Peaks and magnitude of diurnal rainfall patterns changes seasonally. However, during the months of weak monsoon winds, the high elevation cluster has a constant 1700 LT peak highlighting the strong influence of land/sea breeze and mountain breeze. Clusters shifts towards the direction of the monsoon winds (Northeast monsoon-eastwards, Southwest monsoon-westwards) as monsoon winds strengthen (as in December to January). This study therefore illustrates the viability of TRMM 3B42 to describe the diurnal rainfall pattern in different areas in the Philippines and provide a foundation in validating future results from models.